ISU ANAK BERKEBUTUHAN KHUSUS DALAM PELAKSANAAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Risda; Suardi (STKIP Subang, 2026)
This study aims to analyze the implementation of inclusive education and services for students with special needs (SSN) in primary schools through document analysis, interviews, and student group discussions. The results indicate that the school has inclusive-friendly instructional plans and comprehensive initial assessments that serve as a basis for mapping the needs of students with special needs. Social interactions among students demonstrate acceptance, empathy, and prosocial behavior, reflecting the development of an inclusive classroom climate supported by teachers’ roles in fostering respect for diversity. However, the implementation of inclusion still faces challenges, particularly in the lack of systematic instructional adaptations and the insufficient documentation of collaboration among schools, parents, and special education teachers. These findings reveal a gap between inclusive values that have developed at a cultural level and the structured management of inclusive services. Therefore, strengthening adaptive instructional planning, multi-stakeholder collaboration, and school policy support is essential to achieve sustainable and meaningful inclusive education in primary schools.